Normal Tissue Complications following Hypofractionated Chest Wall Radiotherapy in Breast Cancer Patients and Their Correlation with Patient, Tumor, and Treatment Characteristics - Khan, Mohsin; Siddiqui, Shahid A; Gupta, Manoj K; Seam, Rajeev K; Gupta, Manish (Indian Journal of Medical and Paediatric Oncology, 2017)
Introduction: Normal tissue complications following chest wall radiotherapy (RT) are inevitable, and the long-term data on hypofractionation are still limited. To quantify the late effects of hypofractionated RT on cardiac, pulmonary, brachial plexus, and regional lymphatics and their correlation with patient, tumor, and treatment characteristics is the main objective of this study. Materials and Methods: Two hundred and sixteen breast cancer patients following mastectomy were treated with hypofractionated schedules either 40 Gy in 15 fractions or 42.5 Gy in 16 fractions. Common Toxicity Criteria version 3.0 was utilized to quantify the late effects of hypofractionation on cardiac, pulmonary, brachial plexus, and lymphedema at a maximum follow-up of 5 years. Results: Median follow-up was 42 months. Median age was 49 years. 14.8% developed ≥Grade (Gr) 2 late cardiac toxicity. 10.2% developed ≥Gr2 late pulmonary toxicity. There were 28.7% patients who developed ≥Gr2 lymphedema. Sixty-seven out of 216 patients had symptomatic brachial plexopathy at 5-year follow-up. Variables found to increase the incidence of these adverse events included smoking, hypertension, diabetes mellitus, body mass index ≥25, extent of axillary dissection, and use of supraclavicular field. Conclusion: Hypofractionation leads to increased risk of normal tissue complications partly influenced by some patient- and treatment-related factors, but these were manageable and minimally disabling.
Keywords: Breast cancer; hypofractionation; postmastectomy